Molecular cloning and in silico analysis of the duck (Anas platyrhynchos) MEF2A gene cDNA and its expression profile in muscle tissues during fetal development - Liu,Hehe (2012)
The role of myogenic enhancer transcription factor 2a (MEF2A) in avian muscle during fetal development is unknown. In this work, we cloned the duck MEF2A cDNA sequence (GenBank accession no. HM460752) and examined its developmental expression profiles in cardiac muscle, non-vascular smooth muscle and skeletal muscle. Duck MEF2A cDNA comprised 1479 bp encoding 492 amino acid residues. In silico analysis showed that MEF2A contained MADS (MCM1, AGAMOUS, DEFICIENS and SRF -serum response factor), MEF2 and mitogen-activated protein kinase (MAPK) transcription domains with high homology to related proteins in other species. Modified sites in these domains were conserved among species and several variants were found. Quantitative PCR showed that MEF2A was expressed in all three muscles at each developmental stage examined, with the expression in smooth muscle being higher than in the other muscles. These results indicate that the conserved domains of duck MEF2A, including the MADS and MEF2 domains, are important for MEF2A transcription factor function. The expression of MEF2A in duck smooth muscle and cardiac muscle suggests that MEF2A plays a role in these two tissues.